{[(x-2)*3-2]*3-2}*-2=1
va rog dau coroana
targoviste44:
" *-2 "...?!
Răspunsuri la întrebare
Răspuns de
3
Răspuns de
1
{[(x-2)•3-2]•3-2}•3-2=1
{[(x-2)•3-2]•3-2}•3=2+1
{[(X-2)•3-2]•3-2}•3=3
{[(x-2)•3-2]•3-2}=3:3
[(x-2)•3-2]•3-2=1
[(x-2)•3-2]•3=2+1
[(x-2)•3-2]•3 =3
(X-2)•3-2 =3:3
(X-2)•3-2 =1
(X-2)•3=2+1
(X-2 )•3=3
(X-2)=3:3
X-2=1
X=2+1
X=3
Sper că e corect
{[(x-2)•3-2]•3-2}•3=2+1
{[(X-2)•3-2]•3-2}•3=3
{[(x-2)•3-2]•3-2}=3:3
[(x-2)•3-2]•3-2=1
[(x-2)•3-2]•3=2+1
[(x-2)•3-2]•3 =3
(X-2)•3-2 =3:3
(X-2)•3-2 =1
(X-2)•3=2+1
(X-2 )•3=3
(X-2)=3:3
X-2=1
X=2+1
X=3
Sper că e corect
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă